ANALYSIS OF THE CHALLENGES OF ISLAMIC RELIGIOUS EDUCATION IN PUBLIC SCHOOLS IN FORMING NATIONAL CHARACTER - Anri Naldi (Adisam Publisher, 2025)
This research aims to analyze the challenges faced in Islamic Religious Education (PAI) in public schools in the context of national character formation. The method used is a literature review which involves analysis of various sources such as books, journals, articles and other related documents. This research identified several main challenges, including PAI curriculum and materials, teaching methods, teacher qualifications and competencies, learning environment, technology integration, and evaluation and reflection. The results of the study show that the PAI curriculum often does not fully integrate national values, requiring more substantial adjustments. Teaching methods that are less interactive are also an obstacle in attracting students' interest in PAI learning. Varying teacher qualifications and a lack of adequate training programs add to the complexity of this challenge. On the other hand, the learning environment in public schools often does not optimally support a national atmosphere. The use of technology is also not optimal in PAI learning, which actually has the potential to increase student engagement and understanding. Finally, evaluation and reflection on the PAI program must be carried out periodically to ensure the effectiveness and relevance of education in forming national character. In conclusion, although there are various challenges, with a holistic approach and the right strategy, Islamic Religious Education in public schools has great potential in forming students' strong national character.